Networked governance : the future of intergovernmental management - Meek, Jack W.; Thurmaier, Kurt M., 1957- (CQ Press, 2012)
In this volume students can see just how much the landscape of intergovernmental relations has evolved in recent years, with diminishing vertical flows of resources, and increased horizontal flows in the form of cross-jurisdictional and interlocal collaboration.